Human visceral leishmaniasis and relationship with vector and canine control measures - Danielle Nunes Carneiro Castro Costa; Patricia Marques Moralejo Bermudi; Lilian Aparecida Colebrusco Rodas; Caris Maroni Nunes; Roberto Mitsuyoshi Hiramoto; José Eduardo Tolezano; Rafael Silva Cipriano; Graziela Cândido Diniz Cardoso; Cláudia Torres Codeço; Francisco Chiaravalloti Neto (Universidade de São Paulo, 2018)
ABSTRACT OBJECTIVE Estimate the coverage of control measures of visceral leishmaniasis and relate them with the occurrence of human visceral leishmaniasis in endemic urban area. METHODS Cases of human and canine visceral leishmaniasis were considered as study population and evaluated by a serological survey conducted in Araçatuba, state São Paulo, from 2007 to 2015. The cases of human visceral leishmaniasis were geocoded by the address of the patients and the canine disease by the address of the dogs' owners. The coverage of serological survey, euthanasia, and insecticide spraying was calculated, as well as the canine seroprevalence and the incidence rates of human visceral leishmaniasis. The relationship between human visceral leishmaniasis and control measures was evaluated, as well as the seroprevalence by comparing maps and by linear regression. The relationship between the canine and the human disease was also evaluated by the Ripley's K function. RESULTS The incidence rates of human visceral leishmaniasis showed a period of decline (2007 to 2009) and a period of stability (2010 to 2015), a behavior similar to that of canine seroprevalence. In general, the coverage of control measures was low, and the non-association with the incidence of human visceral leishmaniasis can be a result of the period analyzed and of the small number of analyzed units (sectors of the Superintendence for the Control of Endemic Diseases). The distribution of human cases showed spatial dependence with the distribution of seropositive dogs from 2007 to 2009. CONCLUSIONS This study reaffirmed the relationship between the occurrence of the disease in humans and dogs, it verified a decrease in the rates of visceral leishmaniasis in Araçatuba over time, even at low coverage of control activities. However, further studies are needed to determine if factors beyond monitoring and control measures are involved in the reduction of incidences.